한국 성인에서 수면양상, 일주기 유형과 우울증상 간의 상관관계 - 김동희; 강태욱; 고상현; Kim, Dong Hee; Kang, Tae Uk; Koh, Sang Hyun (Journal of the Korean Society of Biological Psychiatry, 2021)
Objectives The aim of this study was to examine the association between the sleep pattern, chronotype (midpoint of sleep on free days) and the depressive symptoms in adults aged 19 years and over in Korea. This study also investigated the mediating effect of perceived usual stress (PUS) and self-rated health (SRH) on the association between chronotype and depressive symptoms. Methods Among the subjects of the 7th Korea National Health and Nutrition Examination Survey (KNHANES) 2016 and 2018, 16142 adults aged 19 or over responded to the survey and finally 8604 were analyzed according to the exclusion conditions. Logistic regression analysis was conducted to see the risk of depressive symptoms, suicidal ideation over sleep pattern, chronotype. Finally, mediation analysis was performed in order to clarify how PUS and SRH are associated to chronoytpe and depression. Results After controlling for potential covariates, weekly sleep duration < 5 hours, ≥ 10 hours was associated with depressive symptoms. And late bed time sleeping after am 1:00 and later midpoints of sleep was associated with a higher level of depressive symptoms. Additionally, the PUS and SRH between chronotype and depressive symptoms showed a serial multiple mediation effect. Conclusions Short or long sleep duration, late bed time and later midpoints of sleep on free days are associated with depressive symptoms. Furthermore, the mechanism between chronotype and depressive symptoms needs to be further clarified by identifying the serial multiple mediation effects of PUS and SRH.